PUNCTURE CRYODESTRUCTION UNDER THE ULTRASOUND GUIDANCE FOR TREATMENT OF RELAPSING FACIAL BASALIOMAS - A. M. Belyayev; G. G. Prokhorov; A. S. Madagov; M. I. Khadziyeva; Z. A. Radzhabova (Неотложная медицинская помощь, 2016)
Basal cell carcinoma is the most frequent human skin malignant tumor. The risk of recurrence exists regardless of the treatment method. The ultrasound assisted treatment in patients with face and neck skin basalioma is analyzed in this study. It was shown that the ultrasound assisted method with usage of modern domestic equipment allowedincreasing the treatment effi cacy of recurrent basal cell skin cancer.